2018
DOI: 10.1017/s1463423618000282
|View full text |Cite
|
Sign up to set email alerts
|

Are the resources adoptive for conducting team-based diabetes management clinics? An explorative study at primary health care centers in Muscat, Oman

Abstract: A cross-sectional study was conducted with 26 public primary health care centers in Muscat, the capital of Oman. Data were collected from manual and electronic resources as well as a questionnaire that was distributed to the physician-in-charge and diabetes management team members.FindingsThe study revealed significant differences between professional groups regarding how they perceived their own competencies, values and skills as well as available resources related to team-based diabetes management. The perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Therefore, these weaknesses that were identified in this study were also reported in the literature, and it should be added that the majority of practicing nurses in clinical settings have less than a baccalaureate degree and may not have been exposed to formal research literature. Furthermore, the incompetent knowledge and skills which were found in our setting and confirmed by a previous study in this project [8] contributed to the nurses' weaknesses and needs for their training to be updated and revised.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Therefore, these weaknesses that were identified in this study were also reported in the literature, and it should be added that the majority of practicing nurses in clinical settings have less than a baccalaureate degree and may not have been exposed to formal research literature. Furthermore, the incompetent knowledge and skills which were found in our setting and confirmed by a previous study in this project [8] contributed to the nurses' weaknesses and needs for their training to be updated and revised.…”
Section: Discussionsupporting
confidence: 72%
“…The gender imbalance could be explained in relation to the higher number of female providers compared to their male counterparts at primary health care centres. [8] The health care providers who were of mixed nationalities (physicians) provided more perceptions and feedback towards the models of care compared to other providers, who were all Omanis, and this could be explained by experiences from their countries of origin and by the Omani physicians' specialization, which was gained from abroad. The interviews were conducted in a professional way, with maximum research ability, despite the hierarchical perception towards physicians at Ministry of Health, and all providers were given voices and chances to express their perceptions equally, which gave them a sense of importance and validity in the diabetes management team.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, community-based diabetes management, although varying in approach under different health systems [7][8][9][10], is an important strategy for the control of diabetes. A large number of programs have demonstrated the enormous role of community-based diabetes management in delaying complications and avoiding hospital admissions [11,12].…”
Section: Introductionmentioning
confidence: 99%